Interactive land-use planning in Indonesia rainforest landscapes: reconnecting plans to practice - Wollenberg, Eva Karoline; Campbell, Bruce M.; Dounias, E.; Gunarso, Petrus; Moeliono, M.; Sheil, Douglas (2009)
Indonesia's 1999-2004 decentralization reforms created opportunities for land-use planning that reflected local conditions and local people's needs. We report on seven years of work in the District of Malinau in Indonesian Borneo that attempted to reconnect government land-use plans to local people's values, priorities, and practices. Four principles are proposed to support more interactive planning between government and local land users: Support local groups to make their local knowledge, experience, and aspirations more visible in formal land-use planning and decision making; create channels of communication, feedback, and transparency to support the adaptive capacities and accountability of district leadership and institutions; use system frameworks to understand the drivers of change and resulting scenarios and trade-offs; and link analysis and intervention across multiple levels, from the local land user to the district and national levels. We describe the application of these principles in Malinau and the resulting challenges.